PASAR MODAL, SAHAM DAN TRADING FOREX MENURUT ISLAM - K.Z, Fina (LIPI, 2014)
Capital market has a strategic position in the national economic development. The growth of a capital market is highly dependent on the performance of securities firms. To coordinate capital, technical support, and human resources in the development, capital markets needed to organize exchanges effectively. Capital Markets provides a wide range of alternatives for investors in addition to other investment alternatives, such as savings in banks, buying gold, insurance, land and buildings, stock, forex trading and so on. Capital market investors act as a liaison with the company or government institutions through long-term trading instruments such as bonds, stocks, and other. This journal will be discussed further.